The Development and Effectiveness of the Innovation “4 in 1 Infant Manikin” Intradermal Injection in Infants - prommul, jirarat; Nelson, Warongrong; Perngyai, Chutima; Klerlhee, Chanyanuch; Intaranarong, Kritika; Mangme, Tuangporn (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Practicing with simulation mannequins is critical to building the skills and confidence of nursing students, enabling them to perform procedures on real patients accurately and safely. This research aimed to develop an innovative mannequin for practicing intradermal injection skills in infants and to study the effectiveness of this innovative mannequin for practicing intradermal injection skills in infants. Methods This research was a research and development (R&D) process with a sample of 81 third-year nursing students, selected through simple random sampling. The instruments used included the innovative mannequin and equipment, as well as an effectiveness assessment form, which had an item-objective congruence (IOC) value ranging from 0.67 to 1.00 and reliability values of 0.78 and 0.89, respectively. Data were analyzed using mean, standard deviation, frequency, and percentage. Results The innovative mannequin had an exterior part made from natural latex, coated with a mixture of latex and acrylic paint to give the skin and arm shape a realistic appearance. The inside part contained a hollow silicone bag with a diameter of 0.5 cm that held air (simulating the injected fluid) and included a valve to release air after skill practice. The effectiveness of the innovative mannequin found that 78 students had practical injection skills at a good level (96.30%) and had the highest level of overall satisfaction with the innovation (M = 4.72, SD = 0.36). Conclusion and Recommendations This innovative mannequin can be used to support learning in pediatric and adolescent nursing courses, allowing learners to practice independently until they achieve proficiency before performing on actual patients. A recommendation for further development is to enhance the structural accuracy according to anatomical principles.